Children and international crimes: victim vs perpetrator - Wielec, Marcin (The ICC at 25: Lessons Learnt, 2025)
This chapter analyses the issue of children in the context of international crimes, in which a child may be perceived as a victim or sometimes, unfortunately, a perpetrator. However, it is possible for a child to be simultaneously classified as both perpetrator and victim. Such a situation, from the perspective of law – including international law, ethics and morality – is extremely challenging to assess. Following an introduction outlining the problem, considerations related to the concept of the child are presented in the light of basic legal instruments in Poland, followed by those related to the concept of the child in the light of the basic instruments of international law. The next stage of the analysis covers international crimes from the perspectives of both Polish and international law. All of the above provides a basis for discussing the topic of children as victims and as perpetrators of crimes. These considerations are supported by an overview of court cases before the International Criminal Court (those of Thomas Lubanga Dyilo, Bosco Ntaganda, and Dominic Ongwen). Positive facts will also be presented. Arising from the research conducted, factors influencing the development of child soldiers will be proposed. The chapter concludes with a concise summary. Keywords: children, international crimes, International Criminal Court, international criminal law, Poland